2019
DOI: 10.1136/jclinpath-2019-205764
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of radial scar/complex sclerosing lesion associated with epithelial proliferations with atypia diagnosed on breast core biopsy: results from a multicentric UK-based study

Abstract: AimsThe clinical significance of radial scar (RS)/complex sclerosing lesion (CSL) with high-risk lesions (epithelial atypia) diagnosed on needle core biopsy is not well defined. We aimed at assessing the upgrade rate to ductal carcinoma in situ (DCIS) and invasive carcinoma on the surgical excision specimen in a large cohort with RS/CSL associated with atypia.Methods157 women with a needle core biopsy diagnosis of a RS/CSL with atypia and follow-up histology were studied. Histological findings, including diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
11
0
2
Order By: Relevance
“…In contrast, the rate of upgrade was 14% (four of 29) for RS with associated atypia. The proportion of RS without atypia or malignancy that we found ( The upgrade rate for RS associated with atypia in this study was 14%, which is within the range of upgrade rates reported previously (upgrade rate of 35% [38 of 108] for RS with atypical ductal hyperplasia [32] and upgrade rates of 17% [one of six] and 10% for RS with atypia [five of 49] [33,34]). These upgrade rates support surgical excision as an optimal management decision for patients with RS with atypia at biopsy.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In contrast, the rate of upgrade was 14% (four of 29) for RS with associated atypia. The proportion of RS without atypia or malignancy that we found ( The upgrade rate for RS associated with atypia in this study was 14%, which is within the range of upgrade rates reported previously (upgrade rate of 35% [38 of 108] for RS with atypical ductal hyperplasia [32] and upgrade rates of 17% [one of six] and 10% for RS with atypia [five of 49] [33,34]). These upgrade rates support surgical excision as an optimal management decision for patients with RS with atypia at biopsy.…”
Section: Discussionsupporting
confidence: 87%
“…In one study of DBT-biopsied RS by Martaindale et al, a similar upgrade rate of 2.8% (one of 36) was reported for cases without atypia at biopsy (33). Interestingly, Rakha et al demonstrated that the upgrade rate for RS and concurrent atypical ductal hyperplasia was similar to the upgrade rate of atypical ductal hyperplasia alone (32), supporting the hypothesis that atypical ductal hyperplasia is likely the main contributor to malignant potential.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In their opinion, VAE is always recommended in cases of RS with atypia, and if no additional atypia is found, surveillance with annual mammography is suggested. In cases where further atypia is found, the management should include open surgical excision [57]. In an interesting study of Özçağlayan et al [58], breast lesion excision system (BLES) has been evaluated as a secure procedure that can provide high diagnostic success and serve as a therapeutic method in high-risk lesions, such as RS, with high complete excision rates.…”
Section: Managementmentioning
confidence: 99%
“…In this setting, imaging-based follow-up is appropriate. 44 Rhaka et al 45 found that the overall upgrade rate to carcinoma on excision following core biopsy of a high-risk RS/CSL was nearly 25% and was highest for ADH in which the upgrade rate was similar to that of ADH not occurring in the context of an RS/CSL. They concluded that the management of RS/CSL should be based on a concurrent atypical lesion detected at core biopsy.…”
Section: Rs/csl Including So-called Iementioning
confidence: 99%